The impact of COVID-19 on and recommendations for breast cancer care: the Singapore experience. Issue 9 (September 2020) - Chan, Jack Junjie; Sim, Yirong; Ow, Samuel Guan Wei; Lim, Joline Si Jing; Kusumawidjaja, Grace; Zhuang, Qingyuan; Wong, Ru Xin; Wong, Fuh Yong; Tan, Veronique Kiak Mien; Tan, Tira Jing Ying
Abstract : The ensuing COVID-19 pandemic poses unprecedented and daunting challenges to the routine delivery of oncological and supportive care to patients with breast cancer. Considerations include the infective risk of patients who are inherently immunosuppressed from their malignancy and therapies, long-term oncological outcomes from the treatment decisions undertaken during this extraordinary period, and diverted healthcare resources to support a coordinated whole-of-society outbreak response. In this review, we chronicle the repercussions of the COVID-19 outbreak on breast cancer management in Singapore and describe our approach to triaging and prioritising care of breast tumours. We further propose adaptations to established clinical processes and practices across the different specialties involved in breast oncology, with references to the relevant evidence base or expert consensus guidelines. These recommendations have been developed within the unique context of Singapore's public healthcare sector. They can serve as a resource to guide breast cancer management for future contingencies in this city-state, while certain elements therein may be extrapolatable to other medical systems during this global public health emergency.